2017
DOI: 10.1038/modpathol.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Mapping clinicopathological entities within colorectal mucinous adenocarcinomas: a hierarchical clustering approach

Abstract: The aim of this study was to interrogate the heterogeneity of colorectal mucinous adenocarcinomas. This study is based on hierarchical clustering approach combining clinicopathological and molecular patterns known to be relevant to oncogenesis and therapeutic management of patients with colorectal carcinoma, ie, microsatellite instability, O6-methylguanine-DNA methyltransferase (MGMT) status, KRAS, and BRAF mutations and wnt signaling pathway activation. Comparison of the study group of 60 mucinous adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(62 reference statements)
1
13
1
1
Order By: Relevance
“…), of which 121 articles were found ineligible. The remaining 46 articles with information on 17 746 patients were deemed suitable for inclusion in the systematic review and meta‐analysis. All included studies had Newcastle–Ottawa scores of between 6 and 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), of which 121 articles were found ineligible. The remaining 46 articles with information on 17 746 patients were deemed suitable for inclusion in the systematic review and meta‐analysis. All included studies had Newcastle–Ottawa scores of between 6 and 9.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have tried to determine the genetic aetiology of mucinous adenocarcinoma of the colon and rectum, with heterogeneous outcomes. Mutations in Kirsten rat sarcoma viral oncogene ( KRAS ) and v‐Raf murine sarcoma viral oncogene homologue B ( BRAF ), inherited defects or epigenetic silencing of mismatch repair (MMR) proteins resulting in microsatellite instability (MSI), and the presence of the CpG island methylator phenotype (CIMP) are the most commonly studied genetic aberrations. The presence or absence of each of these genetic markers may have therapeutic and/or prognostic implications for patients with colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Far fewer mCRC casesonly 24%had undergone molecular analysis for KRAS and BRAF mutational status. Recent studies have reported intriguing results regarding molecular findings in mCRC; most notably, Liddell et al 37 suggested that mCRC can be split into four distinct subtypes depending on clinical and molecular factors. Our lack of molecular data in most cases precluded us from evaluating our cases in a similar, statistically sound manner.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to unravel the genetic etiology of mucinous adenocarcinoma of the colon and rectum by predominantly focusing on mutations in Kirsten rat sarcoma viral oncogene ( KRAS) , v‐Raf murine sarcoma viral oncogene homolog B ( BRAF ), inherited defects or epigenetic silencing of mismatch repair (MMR) proteins resulting in microsatellite instability (MSI) and the presence of the CpG island methylator phenotype (CIMP) . Mucinous tumors have been shown to be associated with an increased rate of BRAF mutations, MSI and CIMP and negatively associated with altered TP53 expression but little else has been described about the genetic mechanisms of these tumors beyond this .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to unravel the genetic etiology of mucinous adenocarcinoma of the colon and rectum by predominantly focusing on mutations in Kirsten rat sarcoma viral oncogene (KRAS), v-Raf murine sarcoma viral oncogene homolog B (BRAF), inherited defects or epigenetic silencing of mismatch repair (MMR) proteins resulting in microsatellite instability (MSI) and the presence of the CpG island methylator phenotype (CIMP). [10][11][12][13][14][15][16] Mucinous tumors have been shown to be associated with an increased rate of BRAF mutations, MSI and CIMP and negatively associated with altered TP53 expression but little else has been described about the genetic mechanisms of these tumors beyond this. 17 This study provides a more in-depth explanation of the genomic aberrations in mucinous adenocarcinoma by focusing on a greater number of genes and by providing analyses on copy number alteration (CNA) and oncogenic signaling pathways in an attempt to discern the molecular mechanisms driving the mucinous phenotype.…”
Section: Introductionmentioning
confidence: 99%